Atopy predisposing to acute bronchiolitis during an epidemic of respiratory syncytial virus. Issue 6322 (10th April 1982) - Laing, I; Reidel, F; Yap, P L; Simpson, H
Abstract : Thirty-one infants admitted to hospital with acute bronchiolitis during an epidemic of respiratory syncytial virus were compared with a control group of 32 infants to establish whether the two groups differed in atopic background. Past history of respiratory illness, eczema, and present reactions to skin testing differed significantly between the two groups. Thus, infants with acute bronchiolitis had a significantly higher atopic predisposition than the controls.